Forestry education in Malaysia: trends and challenges - Ibrahim, Faridah Hanum; Abd. Ghani, Awang Noor (Forestry Department Peninsular Malaysia, 2015)
The expansion of the forestry sector in Malaysia and the importance of forest for its biodiversity conservation and ecosystem services requires the development of human capital at both technical and professional levels. The relevance of forestry education in the country, its trends and challenges are herein discussed.